The place of natural resources in the model of transition to a green economy in Azerbaijan - Humbatova Sevil (BIO Web of Conferences)
The article explores the role of natural resources in the model of transition to a green economy in Azerbaijan, emphasizing the importance of rational resource use and the implementation of new technologies. A key component of the green economy index is the “natural resources group” sub-index, which includes 10 sub-indicators: volumes of fresh water, water consumption, oil and gas production, land fund structure, fishing, and forest areas. The author also highlights methodological issues that arise in comparative studies, including the dependence of some indicators' absolute values on the size of the country and geographical location. To provide a more accurate assessment of the state of natural resources, the article uses the volume of renewable freshwater per capita, which better reflects the potential for transitioning to a green economy. In conclusion, the article proposes refined indicators for assessing the “natural resources group” based on more reliable data, such as the share of hydrocarbon revenues in GDP, allowing for a deeper understanding of the impact of natural resources on sustainable development in Azerbaijan.